Jianjue yonghu Zhongyang guanyu chuli 'Falun Gong' feifa zuzhide jueding - Cheng Guoying,
'Firmly support the decision of the Central Committee to deal with the illegal organization of 'Falun Gong'. Printno. 85410.3590. Anti Falun Gong.